Grammatical Errors in English for Office BLK Instructional Materials - Kapu, Konstantinus; Muliandari, Endah Dewi; Nirmala, Deli (PAROLE: Journal of Linguistics and Education, 2018)
English for Office is one of the programs that is conducted by Balai Latihan Kerja (or BLK for short) or Vocational and Education Training Center (VETC) in Kajen, Pekalongan. BLKhas30 students who prepare their English to work at offices. The English materials are supplied by BLK staff. This paper aims at finding out errors and interlanguage phenomena which occur in the English for Office material used at BLK training. The data were collected by observing the English for Office material at BLK. The result shows that the English for Office materialsat BLKhave grammatical errors, inter-language issues, and sentence or item ambiguity. The grammatical errors consist of misused forms and ambiguous words. From the study, it can be recommended that there should be a proofreading and try out process in order that the materials have met quality control conditions.Â